IMPLEMENTATION OF THE POLICY ISLAMIC EDUCATION IN INDONESIA - Amirsyah Tambunan (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Education is a conscious process to humanize humanity whose activities will fundamentally develop and develop human interests. It is in the human interest to build a noble human civilization based on a clear conscience to return to human identity. The direction of educational policy is to humanize humans through students in line with Islamic values, namely those who are able to optimize their potential to become people who believe and are devoted to Allah SWT. To achieve this ideal of humanizing humans, the role of Islamic educational institutions is especially needed by policy makers and all stakeholders, in this case the government together with the Indonesian Ulema Council (MUI) and institutions directly related to Islamic education. Therefore, Islamic education policy is all educational institutions starting from Kindergarten (TK) to tertiary institutions because these educational institutions will form human values towards complete intelligence. Policies to implement Islamic education in this context must be the main focus amidst the complex challenges facing the world of Islamic education.